Lipidomic analysis reveals serum decreased level of several species of phosphatidylinositol in Schistosoma mansoni high burden-infected patients - Fialho, Thainá Rodrigues de S. (2022)
Fundação Oswaldo Cruz (FIOCRUZ), Instituto Gonçalo Moniz (IGM). Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq).